2021
DOI: 10.3897/folmed.63.e60055
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Nephrin and Podocalyxin Levels as Predictors of Pre-eclampsia in High-Risk Pregnant Women

Abstract: Introduction: Pre-eclampsia (PE) is characterized by new-onset hypertension and proteinuria. Damage of podocyte cells has been reported in pre-eclamptic women, thus podocyte specific proteins such as nephrin and podocalyxin could be useful biomarkers in PE. Aim: To investigate the role of urinary nephrin (u-nephrin) and urinary podocalyxin (u-PDX) levels in predicting PE in women with a high-risk pregnancy. Materials and methods: We included 101 pregnant women in this study and allocated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 30 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…All studies determining urinary nephrin showed that it increased significantly in patients with increased levels of albumin in urine [24,36]. Likewise, other studies have also shown that urinary nephrin increased linearly with the progression of the disease, this suggests that quantification of nephrin could be a useful biomarker of glomerular injury progression [25,47,49].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies determining urinary nephrin showed that it increased significantly in patients with increased levels of albumin in urine [24,36]. Likewise, other studies have also shown that urinary nephrin increased linearly with the progression of the disease, this suggests that quantification of nephrin could be a useful biomarker of glomerular injury progression [25,47,49].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an important aspect to include in a meta-analysis such as this is the heterogeneity in diagnostic accuracy of the methods employed by the various studies. ELISA was the method of choice in most studies (n = 11) for the detection of nephrinuria in PE and nephropathies [20,24,25,31,32,36,43,45,[48][49][50]. Interestingly these assays demonstrated improved sensitivity (0.89) and specificity (0.73) and therefore diagnostic accuracy (AUC-SROC = 0.92) for determining urinary nephrin compared to RT-PCR [44,46,47].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations